Cardiac rehabilitation: into the future. Issue 23 (8th October 2009) - Thompson, D R; Clark, A M
Abstract : Cardiac rehabilitation is increasingly recognised as an integral component of comprehensive cardiac care. The evidence supporting its effectiveness in reducing morbidity and mortality and improving quality of life is compelling. Yet, despite this recognition and exhortations that its implementation should be a key priority, most cardiac patients do not receive rehabilitation. Service provision varies markedly and many programmes are focused on select populations, often operate in an inflexible manner and fail to add potential value. Issues of suboptimal referral, enrolment and completion are poorly addressed and the potential for embracing novel methods and the latest technology are rarely exploited. This paper reviews the current status of cardiac rehabilitation and proposes ways to improve access and uptake and reduce inequity to ensure that those who are likely to benefit from this complex intervention do so.